PENGARUH PROFITABILITAS, KEBIJAKAN HUTANG, KEPUTUSAN INVESTASI, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Novi Perwitasari, 15.05.52.0063; Nurhayati, Ida (Students' Journal of Accounting and Banking, 2019)
This study aims to empirically examine the effect of profitability, debt policy, investment decisions, and firm size on firm value. The population in this study were LQ 45 group companies listed on the Indonesia Stock Exchange in 2015-2017. The total population of this study is 135 and the sample of this study is 117 companies using purposive sampling method. Data experienced an outlier in the normality test so that the data was reduced and became 103 samples of LQ 45 companies listed on the Indonesia Stock Exchange for the period 2015-2017. The analytical tool used is descriptive statistics, normality test, classic assumption test, multiple linear regression test, model test and hypothesis test. Based on the research that has been done the results of this study indicate that profitability has a positive and significant effect on firm value. While debt policy, investment decisions, and company size have no significant effect on firm value.